All we know of heaven - Rougeau, Rémy (Houghton Mifflin Co., 2001)
It is 1973, and Paul Seneschal is so na ve that he hardly seems to realize that the Sixties have come and gone. Seeking protection from a world he finds overwhelming, he enters a Cistercian monastery near Winnipeg, accepting the ancient code of poverty, chastity, and silence. In this sacred place, where 40 monks live together in close quarters, Paul becomes Brother Antoine, working with Friar Casimir Cochard, the cheesemaker, and later becoming cook. But the peace Paul has sought turns out to be elusive. His fellow monks can be wildly unpredictable Father Ignace Lacan dabbles in pyromania, for instance and once the Royal Canadian Mounted Police enter the property with the Winnipeg police, in search of two criminals who robbed a nearby co-op, Paul must realize that the world is something one can never completely escape. This first work by Rougeau, a cloistered monk with an MFA, is itself a bit of a respite, ably capturing the rhythms of monastic life. But it is no solemn treatise the comic blends seamlessly with the tragic and the dryly humorous prose will appeal even to readers without a great interest in the cloister. Ann Irvine, Montgomery P.L., MD